Entrapment of a metal foreign body in the heart during surgical procedure: A case report and literature review - Wang, Fei; Li, Ting; Yuan, Xinwei; Jiang, Hu (Frontiers in Surgery, 2022)
A rongeur had been used to remove thin bones in both orthopedic surgery and neurosurgery, featured with a tip holding and cutting bone effectively while protecting the underlying instruments. The authors describe a case of a 40-year-old man who proceeded with the second lumbar vertebrae osteotomy and presented to be ankylosing spondylitis with kyphosis and limited mobility for 10 years. During the surgery, we found that the rongeur tip was missing. C-arm fluoroscopy showed the high-density body just in front of the vertebral body intraoperatively. However, the CT scan showed the foreign body migrated to the right auricle of the heart postoperatively. This case is unique in that there was no exact vessel injury detected intraoperatively. There were few reports about the surgical instrument migrating to the heart. Our case showed the rare experience of the function of multidisciplinary collaboration in the migration of foreign bodies in the cervical spinal canal.